Integrasi Sejarah Matematika dalam Pembelajaran Matematika pada Materi Phytagoras - Rahma Rosaliana Saraswati; Nabilla Nurizzah; Pipih Pitnawati; Umi Habibah (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2020)
The study aims to know the integration of mathematics history on mathematics learning in phytagoras material to motivate students on mathematics learning. This study is a descriptive qualitative research with data collection of literature review. The integration mathematics history in mathematics learning can be in a form of utilization of problems and solution that is inspired from math history, utilization of anecdote or stories from history to inspire, utilization of mathematics problems in history as a source of question, etc. Mathematical concept was created from necessity to solve problems in daily basis and that concept can grow along with the growing of needs and knowledge by the humans themselves.Mathematics history as an aid in learning process, can give a new experience for the students and make mathematics learning more meaningful because of the relation of daily activities.